Analisis Kebutuhan Zona Selamat Sekolah (ZoSS) MIN 1 Kecamatan Peusangan Kabupaten BireuenAnalysis of Safe School Zone (ZoSS) Needs: A Study of MIN 1 Peusangan Subdistrict, Bireuen Regency - Idayani; Zuraihan; Royanna Sakura (Fakultas Teknik - Universitas Al Muslim - Bireuen Aceh- Indonesia, 2025)
As the number of vehicles traveling back and forth on the road increases, the feeling of safety among road users decreases. Vehicles sometimes ignore the traffic signs that have been provided. These traffic signs are used as guides for road use so that comfort can be created for road users. In order to solve the above problems, it is necessary to implement the ZoSS (School Safe Zone) program. The aim of this research is to determine the condition of traffic signs, road markings and School Safe Zone (ZoSS) facilities compared to existing standards and the level of performance of ZoSS use on the MIN 1 road section, Peusangan District, Bireuen Regency. The method used in this research is the Department of Transportation Regulations (2009). The results of the research show that the level of comfort on Jalan Almuslim-Geulanggang Labu, Peusangan District, Bireuen Regency in the ZoSS area is not yet optimal, because there are still many traffic signs that are not complete and adequate, the average speed is 24.42 km/hour, the maximum speed has been set by the Directorate General of Land Transportation, namely 25 km/hour, this shows that the ZoSS area is safe from passenger cars, the highest vehicle traffic volume was on Monday 10 July 2023, namely 2200 pcu/hour and the road service level is B to A.